(untitled) (Scientific journal of the Fergana State University, 2026)
The article explores the concepts, types of “harassment and violence”, the meaning and essence of the concept of “domestic violence”, conceptual foundations, signs, legal framework for its prevention. The article also covers philosophical aspects of the philosophical-anthropological features of the conformism factor in the Prevention of freshness and violence in family relations.